Using virtual reality for halal slaughtering via medic training simulation and analysis - Abdullah, Lili Nurliyana (2011)
As computer-assisted virtual reality (CAVR) use has increased during the past few years, educators have expressed concern regarding its effectiveness. The purpose of this quasiexperimental study was to determine if completion of a computerized simulation about halal slaughtering animals for food increased slaughter man and publics’ selfefficacy about caring halal dietary laws found in Quran. This study provides a method to electronically educate, train, prototype, test and evaluate new enhancements to the public. This study detailed the modeling and simulation of a s etal cow. The primary objectives of the study were to assess the use of the VR simulation by public and to assess the potential learning outcomes of them in their use of the VR simulation. The system will consists of an anatomically computer model of a cow, a simulation engine capable of providing soft-tissue [1] modeling, rigid body dynamics, collision detection and response, haptic force calculations, and a number of user interface and display devices to interact with the user. In this paper we describe a new method for computer dissection on animal as we use a set of techniques from medical image analysis. In this paper, we also describe how to produce a realistic 3D model of the cow from bidimensional (2D) medical images for animal and slaughtering training. This research will also to make recommendations on the technologies required to create a virtual environment for the simulation of an animal dissection procedure incorporating haptic feedback.